MAKNA WARNA DALAM PERIBAHASA BAHASA JEPANG: KAJIAN SEMANTIK KOGNITIF - Wadhrib Wicaksono; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study discusses the meaning of Japanese proverbs that use color. Every Japanese proverb has a variety of meanings contained in it. In this study, we will discuss the meaning of Japanese proverbs that use color. The data from this study is a collection of Japanese proverbs that use color. The method used in this study is a qualitative descriptive method. The source of proverb data from this research comes from the Kotowaza Jiten Online dictionary. The color proverb data found in the Online dictionary reveals 5 colors such as red, blue, black, white, and yellow. The results of the analysis of Japanese proverbs that use color found various color meanings, there are colors that have meanings as blood, young, good, evil, and loud are found in Japanese proverbs.Key Words: Proverb, Colors, Meaning